BMP2-loaded hollow hydroxyapatite microspheres exhibit enhanced osteoinduction and osteogenicity in large bone defects - Xiong L (Dove Medical Press, 2015)
Long Xiong,1 Jianhua Zeng,1 Aihua Yao,2 Qiquan Tu,3 Jingtang Li,1 Liang Yan,4 Zhiming Tang1 1Department of Osteology, People’s Hospital of Jiangxi Province, Nanchang, Jiangxi, People’s Republic of China; 2School of Materials Science and Engineering, Tongji University, Shanghai, People’s Republic of China; 3Department of Osteology, People’s Hospital of Jiujiang County, Jiujiang, Jiangxi, People’s Republic of China; 4Department of Osteology, The Third Hospital of Nanchang City, Nanchang, Jiangxi, People’s Republic of China Abstract: The regeneration of large bone defects is an osteoinductive, osteoconductive, and osteogenic process that often requires a bone graft for support. Limitations associated with naturally autogenic or allogenic bone grafts have demonstrated the need for synthetic substitutes. The present study investigates the feasibility of using novel hollow hydroxyapatite microspheres as an osteoconductive matrix and a carrier for controlled local delivery of bone morphogenetic protein 2 (BMP2), a potent osteogenic inducer of bone regeneration. Hollow hydroxyapatite microspheres (100±25 µm) with a core (60±18 µm) and a mesoporous shell (180±42 m2/g surface area) were prepared by a glass conversion technique and loaded with recombinant human BMP2 (1 µg/mg). There was a gentle burst release of BMP2 from microspheres into the surrounding phosphate-buffered saline in vitro within the initial 48 hours, and continued at a low rate for over 40 days. In comparison with hollow hydroxyapatite microspheres without BMP2 or soluble BMP2 without a carrier, BMP2-loaded hollow hydroxyapatite microspheres had a significantly enhanced capacity to reconstitute radial bone defects in rabbit, as shown by increased serum alkaline phosphatase; quick and complete new bone formation within 12 weeks; and great biomechanical flexural strength. These results indicate that BMP2-loaded hollow hydroxyapatite microspheres could be a potential new option for bone graft substitutes in bone regeneration. Keyword: bone graft, bone regeneration, synthetic bone substitutes